RANCANG BANGUN SISTEM KEMUDI POWER STEERING HIDROLIK SEBAGAI MEDIA PEMBELAJARAN PRAKTEK CHASSIS - Ridhwan, Maulana; Ansori, Aris (Jurnal Rekayasa Mesin, 2021)
The use of delivering material to students. Students who carry out practicum in the Lab. chasiss Mechanical Engineering, State University of Surabaya still does not have a hydraulic power steering system trainer / trainer as a learning medium in chasiss technology courses and especially chasiss practice. The reason we designed the trainer was to improve the students' ability to understand the steering system, especially the type of hydraulic power steering appropriate media can determine success in learning. Learning media are almost never separated from being used by lecturers in. Some components are blocked or covered by other components, so it is quite difficult to learn. the trainer hydraulic power steering system. The results of the hydraulic power steering system trainer test are that when the steering is straight, turning right and left it is concluded that when the steering is straight the pressure on the hydraulic pump does not transmit fluid to the system at a specified rpm, and when the steering wheel turns right the hydraulic pump is fully distribute fluid to the system at rpm 1700 = 60 Psi, 1000 rpm = 30 Psi and 700 rpm = 20 Psi and at the steering wheel turn left 1700 rpm = 50 Psi, 1000 Rpm = 30 Psi and 700 rpm = 20 psi seen at the pressure gauge, The results of the frame vibration test are aimed at 700 = 0.53 m/s2 rpm and an increase at 1700 rpm = 3.53 m/s2. Keywords: Learning Media, Steering System, Hydraulic Power Steering.